2022
DOI: 10.31616/asj.2020.0405
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Approaches in Lumbosacral Spinal Fusion Surgery: A Systematic Review and Meta-Analysis

Abstract: We aimed to systematically review the literature to analyze the differences in posterior lumbar interbody fusion (PLIF), anterior lumbar interbody fusion (ALIF), and transforaminal lumbar interbody fusion (TLIF), focusing on the complications, risk factors, and fusion rate of each approach. Spinal fusion surgery is a well-established surgical procedure for a variety of indications, and different approaches developed. The various approaches and their advantages, as well as approach-related pathology and complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Postoperative infection is one of the most common and serious complications following spinal surgery. The incidence of this complication reported in recent studies ranged from 0.7% to 12% (Olsen et al, 2008;Ter Gunne & Cohen, 2009;Veeravagu et al, 2009;Fei et al, 2016;Lenz et al, 2021). Known risk factors vary, including old age, male sex, and long operation time, and it has been reported that the postoperative infection rate is 1.24-2.15 times higher in cases involving the use of instrumentation than in cases not involving the use of instrumentation (Veeravagu et al, 2009;Fei et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative infection is one of the most common and serious complications following spinal surgery. The incidence of this complication reported in recent studies ranged from 0.7% to 12% (Olsen et al, 2008;Ter Gunne & Cohen, 2009;Veeravagu et al, 2009;Fei et al, 2016;Lenz et al, 2021). Known risk factors vary, including old age, male sex, and long operation time, and it has been reported that the postoperative infection rate is 1.24-2.15 times higher in cases involving the use of instrumentation than in cases not involving the use of instrumentation (Veeravagu et al, 2009;Fei et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Achieving solid fusion at the lumbosacral junction, L5-S1, remains a challenge, especially in a long instrumented fusion to the sacrum. [1][2][3][4] The L5-S1 segment has unique anatomical characteristics such as poor bone quality of the sacrum, complexity of the sacral anatomy, and an anterior inclination. This makes the fixation at the lumbosacral junction potentially weak during the fusion process, thereby increasing the risk of pseudoarthrosis at this segment.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral interbody fusion (LIF) using a lateral access is a widely used surgical technique for various lumbar degenerative diseases, with proven efficacy and safety. 1) In spinal stenosis, LIF can indirectly decompress the spinal canal by restoring the disc height and reducing spondylolisthesis. 2) LIF is also a powerful surgical tool for adult spinal deformity correction.…”
mentioning
confidence: 99%